Impact assessment of communicating seasonal climate forecasts in Kaffrine, Diourbel, Louga, Thies and Fatick (Niakhar) regions in Senegal: Final Report for CCAFS West Africa Regional Program - Lo, HM; Dieng, M. (2015)
Climate information is now an agricultural input just like seeds, fertilizers or equipment which are at the basis of production. In a nutshell, this is what emerges from this assessment report on the CGIAR Program on Climate Change, Agriculture and Food Security (CCAFS) on the transmission of climate information (CI) and relevant agricultural advice to farmers in Kaffrine, Diourbel, Thies, Louga and Fatick administrative regions. Through this project, CCAFS seeks to contribute to improving the resilience of rural people to climate change by mainstreaming climate information more adequately in the planning and implementation of development activities. Thanks to the involvement of the network of community rural radio stations (URAC), CCAFS estimates that two million people have had access to climate information (CI), have used it in whole or in part, and that this has had an impact on their farming practices.